2020
DOI: 10.1016/j.ijhydene.2020.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Dual application of Ti-catalyzed Li-RHC composite for H2 purification and CO methanation

Abstract: Figure S1 -Evolution of the hydrogen storage capacity with the cycle number for Li-RHC-Ti composite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…The gas-solid reaction of CO 2 with alanates was investigated by Hugelshofer et al where the authors observed the formation of intermediates like aluminum formate and methoxy compounds which then got converted into methane and metal oxides as final products [11]. The influences of gas components on other metal hydrides are well investigated [12][13][14][15][16][17][18][19][20][21][22][23][24]. In this work, the influence of different ratios of CO, CO 2 , N 2 on the hydrogen storage performance of the complex metal hydride Na 3 AlH 6 with 4 mol% TiCl 3 , 8 mol% aluminum and 8 mol% activated carbon is explored.…”
Section: Introductionmentioning
confidence: 99%
“…The gas-solid reaction of CO 2 with alanates was investigated by Hugelshofer et al where the authors observed the formation of intermediates like aluminum formate and methoxy compounds which then got converted into methane and metal oxides as final products [11]. The influences of gas components on other metal hydrides are well investigated [12][13][14][15][16][17][18][19][20][21][22][23][24]. In this work, the influence of different ratios of CO, CO 2 , N 2 on the hydrogen storage performance of the complex metal hydride Na 3 AlH 6 with 4 mol% TiCl 3 , 8 mol% aluminum and 8 mol% activated carbon is explored.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the shifts from XRD and FTIR results, we speculate that Li-N-H-Cl could be formed after the reaction by combining the shifts of XRD and FTIR results, which was reported in a previous work and improved the hydrogen storage kinetic and thermodynamic properties of the Li-N-H system. 47,48 ECLAS over LiH. To accomplish the ECLAS cycle over Li 2 NH/LiH, we also performed an electrochemical N 2 fixation on 5 wt % LiH-LNK at a continuous flow of N 2 (15 mL min −1 ) and at a potential of 1.75 V. The tail gas was detected by an online mass spectrum (MS), and the results of the MS signal are shown in Figure 4a.…”
mentioning
confidence: 99%